Implementation of Seismic Sensor to Detect Tank - Supadmana Muda, Nur Rachman (Journal of World Science, 2024)
This study aims to investigate seismic sensors in detecting ground vibrations caused by tank or military vehicle movements. Ground vibrations generated by tank movements have specific characteristics, where the produced frequency remains constant depending on the tank's weight and the area of the track's footprint. The amplitude of these vibrations provides information about the detection range, wherein the larger the amplitude, the closer the detection range to the tank. The method employed involves field experiments or the collection of quantitative data from field trials. Test results indicate that ground vibrations produced by tanks have an average frequency of 332 Hz, depending on the tank's weight and the area of the track's footprint. The average amplitude is 4.3 volts at a detection range of 1000 meters, 5.1 volts at 500 meters, 7.6 volts at 200 meters, 8.8 volts at 100 meters, and 12.1 volts at 50 meters. The implication of this research is that seismic sensors can be effectively used as tools to detect tank or military vehicle movements at different distances. These findings could be beneficial in the development of security systems or early detection in areas vulnerable to potential threats from tanks or military vehicles.